KARAKTERISTIK PERTUMBUHAN AWAL TANAMAN ALPUKAT HASIL SAMBUNG PUCUK AKIBAT PERLAKUAN LAMA PENYIMPANAN DAN PANJANG ENTRES - Mahadwi, Ken Aditya; Widiwurjani, Widiwurjani; Sulistyono, Agus (International Journal of Multidisciplinary Research and Literature, 2024)
Avocado (Persea americana Mill.) propagation is generally done by grafting, and the scion used as the material is usually taken from the mother plant with superior properties. Often, the location of the mother plant is far from the nursery, so the scion must be stored during the delivery process, which causes the grafting to be delayed. This study aims to determine early growth characteristics of avocado plants resulting from scion grafting due to storage duration and length of scion. This study applied a factorial, completely randomized design method involving two treatment factors with three repetitions. The first factor is the scion with various storage durations (0, 3, 6, and 9 days), and the second factor is the length of the scion (5, 7.5, and 10 cm). The observed variables were the age of bud break, number of buds, length of buds, number of leaves and percentage of successful grafts. Interaction between storage duration and scion length affected the age of bud break. A storage duration of 0 days yielded an optimal age for bud break, length of buds, number of leaves, and percentage of successful grafting. A scion length of 10 cm led to the best age of bud break, number of buds, and number of leaves, while a 5 cm length resulted in the optimal length of buds